2019
DOI: 10.32508/stdj.v22i1.1009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro α-glucosidase inhibitory activity of compounds isolated from mangrove Lumnitzera littorea leaves

Abstract: Introduction: Lumnitzera littorea grown at CanGio Mangrove Forest has been investigated. The present study reports the isolation, characterization and evaluation of the alpha-glucosidase inhibitory activity of isolated compounds from Lumnitzera littorea leaves. Methods: Their structures were elucidated by spectroscopic methods (including MS, 1D and 2D–NMR) and comparison with values from the literature. From the n-hexane extract, nine compounds including lupeol (1), betulin (2), betulinic acid (3), olean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The accumulation of sulfates may be organ-specific. In case of the investigated Lumnitzera species, they are found in the roots, which normally are in contact with sea water, while they were not reported from studies on leaves and twigs [26,[29][30][31]. In this study, both species showed similar patterns of sulfated metabolites despite L. littorea is predominantly occurring at well-drained sites with less salinity, and typically growing as a tree, while L. racemosa is more resistant to saline conditions and occurs at the margin of bare salt pans [70] often growing as a shrub.…”
Section: Phytochemcial Analysesmentioning
confidence: 88%
See 2 more Smart Citations
“…The accumulation of sulfates may be organ-specific. In case of the investigated Lumnitzera species, they are found in the roots, which normally are in contact with sea water, while they were not reported from studies on leaves and twigs [26,[29][30][31]. In this study, both species showed similar patterns of sulfated metabolites despite L. littorea is predominantly occurring at well-drained sites with less salinity, and typically growing as a tree, while L. racemosa is more resistant to saline conditions and occurs at the margin of bare salt pans [70] often growing as a shrub.…”
Section: Phytochemcial Analysesmentioning
confidence: 88%
“…The major metabolites detected in samples from both species were ellagic acid derivatives (Figures 1-3, Table 2), mostly O-methylated at different positions. Commonly, ellagic acid derivatives, including ellagitannins, are widespread in Combretaceae: Ellagic acid and several methylated derivatives were previously detected in leaves and twigs of L. racemosa [26,30] and in related species such as, e.g., in Terminalia species which are widely used in traditional medicine [53], in Pteleopsis hylodendron Mildbr. [54] and in Combretum alfredii Hance [55].…”
Section: Phytochemcial Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that chronic inflammation is implicated in the pathophysiology of type 2 diabetes, and therefore, targeting inflammation may ameliorate diabetes, preventing its progression and vascular complications [11,12]. Following up with our interest in research in biological activities as well as phytochemicals of mangrove plants [13,14], the objective of this work was to determine the anti-inflammatory and antidiabetic activities of extracts and isolated compounds from B. parviflora leaves collected in the Can Gio mangrove forest, Vietnam, in order to confirm their pharmaceutical support.…”
Section: Introductionmentioning
confidence: 99%